Implementation of Situational Leadership Style of Principals in 21 St Century Vocational Schools - Husin, Muhammad (International Journal of Economics and Business Management, 2025)
The principal as a leader in the school has a central role in realizing education that meets competencies and competes globally. During the Covid-19 pandemic, the world of education is hit by various problems and challenges of 21st century competencies, therefore it is necessary to have a competent leader who can overcome various problems. One way is to implement the situational leadership style of the principal in vocational schools. The research method in this writing uses a literature review by collecting data from relevant sources such as books, journals, and others. The results of this study are an effective way to implement the situational leadership style of the principal in vocational schools. To implement the situational leadership style, the principal in vocational schools must have adequate competencies plus insight into the needs of the school to face the needs of the 21st century and understand the supporting and inhibiting factors in schools by applying 4 dimensions of situational leadership style. In the end, if implemented properly, it will result in progress in the quality of education in the school. The principal must also improve his abilities by attending principal training anywhere and visiting schools that have succeeded in achieving their vision, mission and goals. The success of the implementation of the principal's situational leadership is also influenced by the positive thinking of the leader.